Nutrition for Your Kidneys - Ranee, Reshmy; Parveen Kaur, Sarjeet Singh; Arif, Jawaid (UNIMAS Publisher, 2020)
Having seen first hand the difficulties suffered by those undergoing dialysis, the author being a dietitian decided to collaborate with UNIMAS Publisher to write a book on Nutrition for your Kidneys. Serving as a dietitian in one of the prominent dialysis centres in Malaysia made her realise that many of those who are undergoing dialysis are not aware of what to eat, importance of a healthy diet and other pertinent issues related to diet which she hopes to address via this book. Many of them seek information from unreliable sources and quacks and it is hoping that this book will be their one stop centre for all kidney failure and dialysis related information. This book also features the frequently aske